Quick detection of cell to cell communication in gram negative bacteria by colour change of polymer matrix entrapping reporter bacteria. (July 2014) - Nasuno, E.; Okano, C.; Limura, K.; Morohoshi, T.; Ikeda, T.; Kato, N.
<x content-type="archive" xml:space="preserve">Abstract</x> Quick and easy bioassay system for detection of N-acyl-L-homoserine lactones (AHLs) became possible by determining colour change of polymer matrix surfaces entrapping Chromobacterium violaceum CV026 cells, which accumulates purple pigment violacein inside cells through cell–cell communication system termed as quorum sensing (QS). The AHL is popularly produced as one of the QS signals to regulate various cell functions, and its concentration increase can lead to activate the QS. Sensitive detection of producing AHLs could be realised on the polymer surfaces as the gradual changing purple because the AHL synthase defective strain CV026 could respond to produce purple violacein in the presence of AHLs derived from other bacteria. The b* coordinate representing the difference between yellow and blue chromas in the CIE-L*a*b* colour space was obviously negatively correlated with absorbance at 585 nm of butanol extracted violacein from cells irrespective of culture time and initial concentration of cells at inoculation. Time evolution of the chroma at the matrix surface expressed in a*, b* plane was investigated to generate a master curve even when the QS was activated with different concentrations of N-hexanoyl-L-homoserine lactone or N-octanoyl-L-homoserine lactone. As compared with the master curve for the culture broth in a*, b* plane, the matrix surface meaningfully expands since the refractive measurement can give intensive signals at the matrix surface during the initial period of the sequential QS activation. The proposed biosensor can detect the AHL within 3–5 h when the AHL mediated QS system of unknown bacteria is about to be activated, where the conventional agar plate assay needs >16 h.